1991
DOI: 10.1136/gut.32.8.956
|View full text |Cite
|
Sign up to set email alerts
|

Acute gall bladder perforation--a dilemma in early diagnosis.

Abstract: Gall bladder perforation is a rare complication of cholecystitis. A definitive diagnosis is uncommon before surgery and the morbidity and mortality associated with this condition are high. We report six patients with gall bladder perforation to show the difficulty of making an early diagnosis. The history and the clinical findings of these patients are reviewed to highlight diagnostic pitfalls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 8 publications
1
50
2
Order By: Relevance
“…8,12,18 Glenn and Moore in their study, reported a mortality rate of gallbladder perforation patients of 42%, while other studies reported that the mortality rates are decreased to 12%-16% owing to the developments in anesthesiology and intensive care conditions. 11,15,25 While in our study 14% mortality was observed.…”
Section: Surgical Procedures and Morbidities Of The Patientscontrasting
confidence: 39%
See 1 more Smart Citation
“…8,12,18 Glenn and Moore in their study, reported a mortality rate of gallbladder perforation patients of 42%, while other studies reported that the mortality rates are decreased to 12%-16% owing to the developments in anesthesiology and intensive care conditions. 11,15,25 While in our study 14% mortality was observed.…”
Section: Surgical Procedures and Morbidities Of The Patientscontrasting
confidence: 39%
“…8,12,14,15 Tanaka et al reported that only one patient had a concrete diagnosis preoperatively in their series of 9 patients. 16 The majority of GBP patients include those who undergo early surgery with the diagnosis of acute cholecystitis.…”
Section: Surgical Procedures and Morbidities Of The Patientsmentioning
confidence: 99%
“…[6][7][8][9] Neimeier classified gall bladder perforation in three categories. [2][3][4][5][6][7][8]  Type-1 (acute): free perforation with generalized peritonitis.…”
Section: Introductionmentioning
confidence: 99%
“…In patients who can sustain a laparotomy, the threshold for an early surgery should be low. 8,9 The mortality associated with GB perforation is quite high.…”
Section: Discussionmentioning
confidence: 99%